2016
DOI: 10.1016/j.scienta.2016.06.005
|View full text |Cite|
|
Sign up to set email alerts
|

Genotyping by sequencing for SNP discovery and genetic mapping of resistance to race 1 of Fusarium oxysporum in watermelon

Abstract: a b s t r a c t Management of fusarium wilt caused by Fusarium oxysporum f. sp. niveum (Fon) (E.F. Sm.) W.C. Snyder & H.N. Han. in watermelon [Citrullus lanatus (Thunb.) Matsum.& Nakai] is largely dependent on cultivation of resistant cultivars. Application of marker-assisted selection (MAS) in conventional breeding programs can accelerate the release of new watermelon cultivars resistant to fusarium wilt. Towards developing tools for MAS, physical (1024 SNPs) and genetic (389 SNPs) maps were developed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
1
14
1
Order By: Relevance
“…Based on this criterion, 501 SNPs were placed on the physical map (Guo et al, 2013) and used for QTL mapping. Meru and McGregor (2016) previously showed that comparable results were obtained when using the physical (markers ordered according to their physical positions) or genetic map to identify QTL associated with FON 1 resistance in watermelon.…”
Section: Methodsmentioning
confidence: 77%
See 4 more Smart Citations
“…Based on this criterion, 501 SNPs were placed on the physical map (Guo et al, 2013) and used for QTL mapping. Meru and McGregor (2016) previously showed that comparable results were obtained when using the physical (markers ordered according to their physical positions) or genetic map to identify QTL associated with FON 1 resistance in watermelon.…”
Section: Methodsmentioning
confidence: 77%
“…niveum race 2. Disease severity was visually rated on a scale of 0 to 5 where, 0 = asymptomatic plants, 1 = initial wilting on one leaf, 2 = continued wilting in more than one leaf, 3 = all leaves wilted, 4 = all leaves wilted and stem collapsing, and 5 = dead plants (Meru and McGregor, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations